Exploring the cognitive effects of kratom: A review - Suhaimi, Farah Wahida; Khari, Nurul Husna Mohamad; Hassan, Zurina; Müller, Christian P. (Behavioural Brain Research, 2025)
Despite the strict kratom regulation in some regions, the demand for kratom products is still increasing worldwide. Kratom products are commonly consumed for their pain-relieving effect or as a self-treatment for opioid use disorder. Kratom is also taken as a recreational drug among youth and adults. Since substance abuse can cause cognitive impairment, many studies investigated the effects of kratom on cognition. The interaction of some kratom alkaloids with various receptors such as opioid, serotonergic, and adrenergic receptors further sparks the interest to investigate the effects of kratom on cognitive function. Hence, this review aims to provide an overview of the effects of kratom on cognitive behaviours and their underlying changes in neurobiological mechanisms. In conclusion, kratom, particularly its main alkaloid, mitragynine may adversely affect cognitive performances that may be attributed to the disruption in synaptic plasticity, brain activity as well as various proteins involved in synaptic transmission. The impact of kratom on cognitive functions could also shed light on its safety profile, which is essential for the therapeutic development of kratom, including its potential use in opioid substitution therapy.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Cognitive behaviors; Kratom; M. speciosa; Mitragynine